Latin American philosophy from identity to radical exteriority - Vallega, Alejandro A. (World philosophies., 2014)
While recognizing its origins and scope, Alejandro A. Vallega offers a new interpretation of Latin American philosophy by looking at its radical and transformative roots. Placing it in dialogue with Western philosophical traditions, Vallega examines developments in gender studies, race theory, postcolonial theory, and the legacy of cultural dependency in light of the Latin American experience. He explores Latin America's engagement with contemporary problems in Western philosophy and describes the transformative impact of this encounter on contemporary thought.